2021
DOI: 10.7150/ntno.51391
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of cell-based therapy using 89Zr-oxine ex vivo cell labeling for positron emission tomography

Abstract: With the rapid development of anti-cancer cell-based therapies, such as adoptive T cell therapies using tumor-infiltrating T cells, T cell receptor transduced T cells, and chimeric antigen receptor T cells, there has been a growing interest in imaging technologies to non-invasively track transferred cells in vivo. Cell tracking using ex vivo cell labeling with positron emitting radioisotopes for positron emission tomography (PET) imaging has potential advantages over single-photon emitting radioisotopes. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…This assumption is supported by a number of studies. Current publications show that Zr-89 is bound intracellularly after it has been able to penetrate the cell wall as a lipophilic complex [ 30 , 31 ]. Fung et al[ 32 ] observed differences in the clearance rates of radioactivity from the tumor for two forms of the humanized monoclonal antibody J591 ([ 124 I]I-J591 and [ 89 Zr]Zr-J591) against prostate-specific membrane antigen (PSMA) in mice with LNCaP tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by a number of studies. Current publications show that Zr-89 is bound intracellularly after it has been able to penetrate the cell wall as a lipophilic complex [ 30 , 31 ]. Fung et al[ 32 ] observed differences in the clearance rates of radioactivity from the tumor for two forms of the humanized monoclonal antibody J591 ([ 124 I]I-J591 and [ 89 Zr]Zr-J591) against prostate-specific membrane antigen (PSMA) in mice with LNCaP tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Meidenbauer et al [ 49 ] labeled Melan-A-specific CD8 + cytotoxic T lymphocytes with [ 111 In]oxine and demonstrated the localization of these radiolabeled cells to metastatic sites 48 h after injection [ 49 ]. More recently, several groups [ 50 , 51 , 52 ] have studied ex-vivo CAR-T cells labeling techniques using [ 89 Zr] for PET imaging. The synthesis and labelling steps are similar to those used for the [ 111 In]oxine complex, but the use of [ 89 Zr] is more promising, owing to the higher spatial resolution, higher sensitivity, and better signal-to-background ratio of PET compared with SPECT, and owing to its comparably long half-life of 3.27 days compared to 2.80 days for 111In, which is helpful to monitor cell distribution in murine models after administration [ 53 ].…”
Section: Molecular Imagingmentioning
confidence: 99%
“…Perhaps the most clinically advanced form of in vivo targeting and also adoptive cell radiolabeling is found in zirconium (89-Zr). 29 Notably more specific than other tracers such as 18-F given its independence from glucose metabolism, 30 89-Zr also has the advantages of a long half-life (3.3 days), making it helpful for tracking Molecular Therapy: Oncolytics Vol. 23 December 2021 cells during at least several days with serial CT-PET imaging.…”
Section: Current Clinical Progress In Tracking Immune Responses To Ovmentioning
confidence: 99%
“…23 December 2021 cells during at least several days with serial CT-PET imaging. 29 Moreover, its relatively lower positron energy fosters enhanced resolution of PET images. While other more specific tracers such as copper are also being studied, the half-life is comparatively short and the background signal is also prohibitive in some cases.…”
Section: Current Clinical Progress In Tracking Immune Responses To Ovmentioning
confidence: 99%